Research on trust measure and management for open distributed systems based on dynamic grouping - Li-ming JIANG; Zhi-ming LIU; Kun ZHANG; Jian XU; Hong ZHANG (Tongxin xuebao)
A stability enhanced group-based trust model(denoted by SEGTM) for open distributed systems was presented to solve the problems of not sufficiently maintaining trust relation between peers due to the dynamic changes in trust network topology.First,the formation and dynamic management of peers' group were depicted in detail,including nodes gathered into the same group with similar interests,competition for group head and nodes within the group leave in active or passive ways.Then,the trust relation in proposed model was categorized into three kinds and subsequently each solution for these kinds was also put forward.So,the problems of decline in accuracy of computational trust degree between peers due to the difference of peers' interests and low probability of repeated transactions between them were addressed.Simulation results show that the model not only enhances the fairness and stability in response to dynamic changes in network topology,but also can effectively resist the attacks of malicious nodes.